Synthesis and Antibacterial Evaluation of Novel 1,3,4-Oxadiazole Derivatives Containing Sulfonate/Carboxylate Moiety - Lei Wang; Xia Zhou; Hui Lu; Xianfu Mu; Linhong Jin (Molecules, 2020)
Abstract: In order to discover new lead compounds with high antibacterial activity, a series of new derivatives were designed and synthesized by introducing a sulfonate or carboxylate moiety into the 1,3,4-oxadiazole structure. Antibacterial activity against two phytopathogens, Xanthomonas oryzae pv. oryzae (Xoo) and Xanthomonas axonopodis pv. citri (Xac), was assayed in vitro. The preliminary results indicated that ten compounds including 4a-1-4a-4 and 4a-11-4a-16 had good antibacterial activity against Xoo, with EC50 values ranging from 50.1-112.5 µM, which was better than those of Bismerthiazol (253.5 µM) and Thiodiazole copper (467.4 µM). Meanwhile, 4a-1, 4a-2, 4a-3 and 4a-4 demonstrated good inhibitory effect against Xanthomonas axonopodis pv. citri with EC50 values around 95.8-155.2 µM which were better than those of bismerthiazol (274.3 µM) and thiodiazole copper (406.3 µM). In addition, in vivo protection activity of compound 4a-2 and 4a-3 against rice bacterial leaf blight was 68.6% and 62.3%, respectively, which were better than bismerthiazol (49.6%) and thiodiazole copper (42.2%). Curative activity of compound 4a-2 and 4a-3 against rice bacterial leaf blight was 62.3% and 56.0%, which were better than bismerthiazol (42.9%) and thiodiazole copper (36.1%). Through scanning electron microscopy (SEM) analysis, it was observed that compound 4a-2 caused the cell membrane of Xanthomonas oryzae pv. oryzae ruptured or deformed. The present results indicated novel derivatives of 5-phenyl sulfonate methyl 1,3,4-oxadiazole might be potential antibacterial agents.